Analysis of Thinking Mathematics Based on Van de Walle's: A Case Study in Students Grade 5th: Analysis of Thinking Mathematics Based on Van de Walle's - Dya Ayu Agustiana Putri; Sugiman Sugiman; Yoppy Wahyu Purnomo (Creative Smart Visionary, 2025)
This study explores fifth-grade students' mathematical thinking processes, specifically how they interpret and solve addition and subtraction problems in story-based contexts. Using a qualitative case study approach, five students from an elementary school in Yogyakarta were examined through interviews, observations, and mathematics problem-solving tasks. The data were analyzed using inductive thematic coding to uncover patterns in computational strategy and conceptual understanding. Results showed that students employed diverse techniques such as horizontal and vertical stacking, semantic and computational sentence transformation, and even-number decomposition. These strategies reflected varying levels of comprehension regarding commutative and associative mathematical properties. Moreover, students who had difficulty translating story problems into mathematical expressions typically showed weak understanding of operational meaning and structure. The study found that most students shifted from semantic to computational forms for ease in calculation. This suggests the need for instructional support to enhance students’ conceptual grasp of operations. Overall, this study provides insights into how mathematical thinking can be developed through contextual learning and supports integrating meaningful problem-solving practices into mathematics education.